Hounsfield unit for assessing bone mineral density distribution within lumbar vertebrae and its clinical values - Chen, Jiabao; Li, Yanhong; Zheng, Han; Li, Haotian; Wang, Haidong; Ma, Lei (Frontiers in Endocrinology, 2024)
Study Design: Retrospective radiological analysis. Objective: The aim of this study is to evaluate the distribution of bone mineral density (BMD) in lumbar vertebrae using the Hounsfield unit (HU) measurement method and investigate the clinical implications of HU values for assessing lumbar vertebrae BMD. Method: Two hundred and ninety-six patients were retrospectively reviewed and divided into six groups according to age: Group 1(20-29 years old), Group 2 (30-39 years old), Group 3 (40-49 years old), Group 4 (50-59 years old), Group 5 (60-69 years old), Group 6 (70-79 years old). Six different locations from each vertebra of L1-L5 were selected as regions of interest: the anterior, middle and posterior parts of the upper and lower slices of the vertebrae. HU values were measured for the six regions of interest, followed by statistical analysis.The HU values of vertebrae showed a decreasing trend from young patients to elderly patients in Group 1 to Group 5. There was no significant difference in HU values among different vertebrae in the same age group. In all age groups, the HU values of the anterior and posterior part of the vertebral body were significantly different from L1 to L3, with the anterior part of the vertebral body having lower HU values than the posterior part. The HU values of the anterior and posterior part of the vertebral body of L4 and L5 were statistically significant only in Group 5 and Group 6, and the HU values of the anterior part of the vertebral body were lower than those of the posterior part. The HU values of posterior part of L4 and L5 in Group6 were higher than those in Group5. Conclusion: Bone mineral density in the lumbar vertebrae is not uniformly distributed, potentially attributed to varying stress stimuli. The assessment of local HU values in the lumbar spine is of significant importance for surgical treatment.